PENGEMBANGAN MODUL BERBASIS POE (PREDICT, OBSERVE, EXPLAIN) MATERI USAHA DAN ENERGI DITINJAU DARI KEMAMPUAN KOGNITIF - Aria Tanti Wika Sari; Dedy Hidayatullah Alarifin (UNIVERSITAS MUHAMMADIYAH METRO, 2016)
Physics to prepare the student to be able to encounter of changes in life. Because it, the student must have an interesting module for students to learn independently at home. One of the model learning is potential of students to solve problems practice is POE. This research is a R&D with the procedural model that